Study on Knowledge, Attitude and Practice of Family Planning among Married Women in the Rangeli Municipality of Morang District, Nepal - Sah, Dr. Ram Bilakshan; Shah, Mrs. Usha; Jha, Dr. Nilambar (International Journal of Innovative Research in Medical Science, 2018)
Introduction: Knowledge about methods of contraception could reduce the level of unwanted pregnancy and unsafe abortion. Particularly, utilization of contraception among married women have beneficiary health outcome as it adds choice for helping sexually active married women to avoid unintended pregnancy and its consequences. Objectives: To find out knowledge, attitude and practice of family planning among married woman in Rangeli Municipality. Methods: The cross-sectional study was conducted among residents of Rangeli Municipality where 400 married women were taken as subjects. Pretested semi-structured questionnaire was administered to the study subjects and face to face interview was conducted. Collected data was entered in Microsoft excel and the analysis was done by using statistical software SPSS (Statistical package for Social Science) 17.0 version. Results: Almost 83.5% of married women have knowledge about prevention of pregnancy by contraception and they use contraception for child spacing (33.5%). Most of the women have the source of knowledge about family planning as media (35.5%) and relatives (35.5%). Majority of them (56.3%) know that OCP is provided free of cost. Majority of the participants (80.8%) and family members (76%) have positive attitude towards family planning. Majority of the women (63.9%) were using permanent method of family planning. Amongst women practicing temporary family planning methods Depo (42.7%) and Oral contraceptives pills (36%) was used most widely. Conclusions: The study concludes that the married women of Rangeli Municipality have good knowledge and favorable attitude towards family planning, but, practice of using contraception was poor. They use contraception for child spacing and majority of the participants were using Depo and Oral contraceptives pills as a temporary method of family planning.